2010
DOI: 10.1534/genetics.110.118166
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Responses to Hypoxia in Drosophila Larvae Are Mediated by Atypical Soluble Guanylyl Cyclases

Abstract: The three Drosophila atypical soluble guanylyl cyclases, Gyc-89Da, Gyc-89Db, and Gyc-88E, have been proposed to act as oxygen detectors mediating behavioral responses to hypoxia. Drosophila larvae mutant in any of these subunits were defective in their hypoxia escape response-a rapid cessation of feeding and withdrawal from their food. This response required cGMP and the cyclic nucleotide-gated ion channel, cng, but did not appear to be dependent on either of the cGMP-dependent protein kinases, dg1 and dg2. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 45 publications
(83 reference statements)
2
52
0
Order By: Relevance
“…It will be interesting to determine whether mutation of IR56a affects motor behavior. Likewise, the IR94d-GAL4 expression pattern resembles the expression pattern of oxygen-sensing cells that function in an escape response elicited by hypoxia (9).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It will be interesting to determine whether mutation of IR56a affects motor behavior. Likewise, the IR94d-GAL4 expression pattern resembles the expression pattern of oxygen-sensing cells that function in an escape response elicited by hypoxia (9).…”
Section: Discussionmentioning
confidence: 92%
“…5F). These neurons may have a chemosensory role in sensing local gas concentrations and in mediating an escape behavior that is triggered by hypoxia or hyperoxia (9,29); more detailed analysis will be required to determine their functional identity. Labeling was occasionally observed in the body wall of other abdominal segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3C). The overall weaker response to oxygen relative to vinegar is expected because prior studies have shown that there are no oxygen-specific sensors in the antennal lobe and the response to oxygen results from either the airflow itself (27) or a decrease in carbon dioxide concentration (28)(29)(30). Finally, we also measured the response to oxygen and vinegar using a time series optimized for rapid imaging of a single plane spanning the cell body region and the calyx (see Materials and Methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…Some examples are the mechanisms through which animals perceive oxygen levels within their environment. For example, environmental oxygen is sensed by specific soluble guanylyl cyclases (sGCs) in specific sensory neurons in C. elegans and Drosophila (Cheung et al, 2005;Chang et al, 2006;Rogers et al, 2006;Vermehren-Schmaedick et al, 2010). These sGCs regulate the aerotactic behaviors of the animals: C. elegans prefers 7-11% ambient oxygen and is repelled by hypoxic (<5% O 2 ) and hyperoxic (>14% O 2 ) environments (Cheung et al, 2005;Chang et al, 2006;Rogers et al, 2006); whereas Drosophila larvae prefer a more restricted range of O 2 concentration (∼21%) (VermehrenSchmaedick et al, 2010).…”
Section: The Effects Of Neuronal Stress-sensing Pathways On Lifespan mentioning
confidence: 99%